Operational challenges to the 1-3-7 surveillance strategy for malaria elimination in China: a qualitative study. (October 2016) - Lu, Guang-yu; Liu, Yao-bao; Beiersmann, Claudia; Feng, Yu; Cao, Jun; Müller, Olaf
Abstract: Background: China aims to eliminate malaria by 2020. In 2012, China launched its 1-3-7 malaria surveillance strategy, which refers to case reporting within one day, case investigation within three days, and focus investigation and public health actions within seven days. The aim of this study was to identify operational challenges to the 1-3-7 surveillance strategy. Methods: This qualitative study was conducted in northwestern (Gansu Province) and southeastern (Jiangsu Province) China. Malaria experts, health staff, laboratory practitioners, and village doctors at the provincial Institutes of Parasitological Disease, provincial Centers of Disease Control and Prevention (CDCs), city CDCs, county CDCs, township hospitals, and village clinics were selected by purposeful sampling and snowball sampling. Interviews of key informants (individuals with good, first-hand knowledge of implementation of the 1-3-7 strategy in the province; n=6) and in-depth interviews (n=36) on malaria case reporting, case investigation, and focus investigation were conducted. The study was approved by the local authorities of the provinces where the study took place in China, and by the Ethical Committee of the Medical School of the Heidelberg University in Germany (S-363/2014). All participants were asked for written informed consent before the interview. Findings: Major challenges identified were decreasing knowledge and vigilance of health staff and the population regarding malaria, technical difficulties of diagnosis of low parasitaemia and asymptomatic cases, absence of or difficulties in following guidelines on specific public health actions during focus investigation, and—most importantly—the increasing number of returning migrant workers from malaria-endemic countries, in particular from Africa. Lack of intersectorial collaboration, missing community participation, and too little engagement of village doctors were among the major problems identified with regard to addressing migrant populations at risk for malaria. Interpretation: Although the Chinese 1-3-7 malaria surveillance strategy has already been shown to be successful, it still faces some important challenges. A major challenge is the increasing number of imported malaria cases. This problem needs to be addressed by better methods to identify migrant workers from malaria-endemic countries and to provide them with well-functioning diagnosis and treatment services. Overall, China has excellent preconditions for successful malaria elimination provided that political commitment and financial investment continue to be guaranteed. Funding: Natural Science Foundation of Jiangsu Province (BK20150001), and Jiangsu Science and Technology Department (BM2015024).